2010
DOI: 10.1007/s00216-010-3724-6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of natural occurrence of the banned antibiotic chloramphenicol in herbs and grass

Abstract: Chloramphenicol (CAP), a broad-spectrum antibiotic, was detected in several herb and grass samples from different geographic origins. Due to its suspected carcinogenicity and linkages with the development of aplastic anemia in humans, CAP is banned for use in food-producing animals in the European Union (EU) and many other countries. However, products of animal origin originating from Asian countries entering the European market are still found noncompliant (containing CAP) on a regular basis, even when there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 6 publications
3
47
0
1
Order By: Relevance
“…It is also possible that unintentional chloramphenicol exposure occurs infrequently (Levy and Marshall, 2004). For example, Berendsen et al (2010) reported natural occurrence of chloramphenicol in plants in Mongolia and the Netherlands. No farmer was found to use chloramphenicol for the current study.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that unintentional chloramphenicol exposure occurs infrequently (Levy and Marshall, 2004). For example, Berendsen et al (2010) reported natural occurrence of chloramphenicol in plants in Mongolia and the Netherlands. No farmer was found to use chloramphenicol for the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Furazolidone is mostly used by farmers in the treatment of salmonellosis as the drug is commonly called a 'wonder drug'. Furazolidone and chloramphenicol in food-producing animals are banned in the United States, United Kingdom and European Union because of their carcinogenicity, mutagenicity and linkages with the development of aplastic anemia in humans (Berendsen et al, 2010;Kabir et al, 2004). Farm owners also administered antibiotics without veterinary consultation mainly because of the cost of veterinary services.…”
Section: Table Imentioning
confidence: 99%
“…Application of a higher dose than that recommended, failure respecting proper withdrawal times, or irresponsible use of the veterinary drugs can result in the occurrence of unwanted residues of drugs in food of animal origin (Shao et al, 2009). The presence of veterinary drugs in food and foodstuffs has been frequently reported (Bando, Oliveira, Ferreira, & Machinski, 2009;Berendsen et al, 2010;Lopez, Pettis, Smith, & Chu, 2008;Sheridan, Policastro, Thomas, & Rice, 2008). Residues of drugs in food can endanger consumers' health.…”
Section: Introductionmentioning
confidence: 97%